1999
DOI: 10.1046/j.1365-2362.1999.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe dietary restriction initiated in aged rats: evidence for poor adaptation in terms of protein metabolism and intestinal functions

Abstract: Aged rats clearly exhibit a defect of adaptation to long-term DR initiated at an advanced age. Severe DR leads to malnutrition, which becomes of major importance after 12 weeks, in particular at the intestine level. Hence, application of these experimental results to elderly, malnourished people may contribute to a better knowledge of denutrition-induced disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
(42 reference statements)
2
13
0
Order By: Relevance
“…The small intestinal mucosa was hypotrophic with reduced mucosal thickness, villus height and crypt depth. Specific activities of lactase, maltase, sucrase and ileal hydrolase were decreased (Firmansyah et al 1989, Chambon-Savanovitch et al 1999.…”
Section: Discussionmentioning
confidence: 97%
“…The small intestinal mucosa was hypotrophic with reduced mucosal thickness, villus height and crypt depth. Specific activities of lactase, maltase, sucrase and ileal hydrolase were decreased (Firmansyah et al 1989, Chambon-Savanovitch et al 1999.…”
Section: Discussionmentioning
confidence: 97%
“…The small intestinal mucosa is hypotrophic with reduced mucosal thickness, villus height and crypt depth are reduced in malnourished rodents. Specific activities of lactase, maltase, sucrase and ileal hydrolase are decreased (Firmansyah 1989, Chambon-Savanovitch et al 1999. It is well documented that male worms intimately control and regulate the expression of a number of female genes (LoVerde & Chen 1991, Skelly et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to middle‐aged patients, weight loss in the elderly involves a preferential decrease in lean body mass and body cell mass that is implicated in clinical outcomes of malnutrition. Furthermore, an experimental study found that old rats exhibited deficient defective adaptation to long‐term 50% dietary restriction initiated at an advanced age, resulting in dramatic body weight loss and deregulation of protein metabolism in terms of nitrogen balance and protein content, especially at skeletal muscle level . Muscle is therefore one the prime targets of malnutrition .…”
Section: Introductionmentioning
confidence: 99%